Breast feeding and intergenerational social mobility: what are the mechanisms?. Issue 9 (24th June 2013) - Sacker, A; Kelly, Y; Iacovou, M; Cable, N; Bartley, M
Abstract : Objective: To investigate the association between breast feeding and intergenerational social mobility and the possible mediating role of neurological and stress mechanisms. Design: Secondary analysis of data from the 1958 and the 1970 British Cohort Studies. Setting: Longitudinal study of individuals born in Britain during 1 week in 1958 and 1970. Participants: 17 419 individuals participated in the 1958 cohort and 16 771 in the 1970 cohort. The effect of breast feeding on intergenerational social mobility from age 10/11 to age 33/34 was analysed after multiple imputations to fill in missing data and propensity score matching on a wide range of confounders measured in childhood (1958 cohort N=16 039–16 154; 1970 cohort N=16 255–16 361). Main outcome measures: Own Registrar General's Social Class (RGSC) at 33/34 years adjusted for father's RGSC at 10/11 years, gender and their interaction. Results: Breastfed individuals were more likely to be upwardly mobile (1958 cohort: OR 1.24 95% CI 1.12 to 1.38; 1970 cohort: OR 1.24 95% CI 1.12 to 1.37) and less likely to be downwardly mobile (1958 cohort: OR 0.81 95% CI 0.73 to 0.90; 1970 cohort: OR 0.79 95% CI 0.71 to 0.88). In an ordinal regression model, markers of neurological development (cognitive test scores) and stress (emotional stress scores) accounted for approximately 36% of the relationship between breast feeding and social mobility. Conclusions: Breast feeding increased the odds of upward social mobility and decreased the odds of downward mobility. Consistent with a causal explanation, the findings were robust to matching on a large number of observable variables and effect sizes were alike for two cohorts with different social distributions of breast feeding. The effect was mediated in part through neurological and stress mechanisms.